let C be Category; :: thesis: for a being Object of C
for f being Morphism of C holds
( hom ((id a),f) = hom (a,f) & hom (f,(id a)) = hom (f,a) )

let a be Object of C; :: thesis: for f being Morphism of C holds
( hom ((id a),f) = hom (a,f) & hom (f,(id a)) = hom (f,a) )

let f be Morphism of C; :: thesis: ( hom ((id a),f) = hom (a,f) & hom (f,(id a)) = hom (f,a) )
A1: cod (id a) = a ;
now :: thesis: ( dom (hom ((id a),f)) = Hom (a,(dom f)) & dom (hom (a,f)) = Hom (a,(dom f)) & ( for x being object st x in Hom (a,(dom f)) holds
(hom ((id a),f)) . x = (hom (a,f)) . x ) )
Hom ((dom f),(cod f)) <> {} by CAT_1:2;
then ( Hom (a,(cod f)) = {} implies Hom (a,(dom f)) = {} ) by CAT_1:24;
hence ( dom (hom ((id a),f)) = Hom (a,(dom f)) & dom (hom (a,f)) = Hom (a,(dom f)) ) by FUNCT_2:def 1; :: thesis: for x being object st x in Hom (a,(dom f)) holds
(hom ((id a),f)) . x = (hom (a,f)) . x

let x be object ; :: thesis: ( x in Hom (a,(dom f)) implies (hom ((id a),f)) . x = (hom (a,f)) . x )
assume A2: x in Hom (a,(dom f)) ; :: thesis: (hom ((id a),f)) . x = (hom (a,f)) . x
then reconsider g = x as Morphism of C ;
A3: dom g = a by ;
A4: cod g = dom f by ;
thus (hom ((id a),f)) . x = (f (*) g) (*) (id a) by
.= f (*) (g (*) (id a)) by
.= f (*) g by
.= (hom (a,f)) . x by ; :: thesis: verum
end;
hence hom ((id a),f) = hom (a,f) ; :: thesis: hom (f,(id a)) = hom (f,a)
now :: thesis: ( dom (hom (f,(id a))) = Hom ((cod f),a) & dom (hom (f,a)) = Hom ((cod f),a) & ( for x being object st x in Hom ((cod f),a) holds
(hom (f,(id a))) . x = (hom (f,a)) . x ) )
Hom ((dom f),(cod f)) <> {} by CAT_1:2;
then ( Hom ((dom f),a) = {} implies Hom ((cod f),a) = {} ) by CAT_1:24;
hence ( dom (hom (f,(id a))) = Hom ((cod f),a) & dom (hom (f,a)) = Hom ((cod f),a) ) by FUNCT_2:def 1; :: thesis: for x being object st x in Hom ((cod f),a) holds
(hom (f,(id a))) . x = (hom (f,a)) . x

let x be object ; :: thesis: ( x in Hom ((cod f),a) implies (hom (f,(id a))) . x = (hom (f,a)) . x )
assume A5: x in Hom ((cod f),a) ; :: thesis: (hom (f,(id a))) . x = (hom (f,a)) . x
then reconsider g = x as Morphism of C ;
A6: cod g = a by ;
thus (hom (f,(id a))) . x = ((id a) (*) g) (*) f by
.= g (*) f by
.= (hom (f,a)) . x by ; :: thesis: verum
end;
hence hom (f,(id a)) = hom (f,a) ; :: thesis: verum